CONVENTIONAL ACCOUNTING VERSUS SHARIA ACCOUNTING: RECONCILIATION OF PERCEPTION TO ACHIEVE SPIRITUAL MEANING - Sandra Iriawan (UNEJ e-Proceeding)
This study was conducted to investigate how far the practice of sharia accounting that developed so far is different from current conventional accounting practice by referring to the desire to understand the reasons why the underlying stereotype of society still consider that accounting practices in sharia banking do not differ substantially with conventional banking. At the same time, doing a reconciliation of perceptions to minimize the perception gap towards the achievement of spiritual significance. This is done by involving the results of the analysis of the practitioners (managers of Islamic financial institutions), academics (lecturers and students), and the standard drafting board (DSAS). Husserl's transcendental phenomenology approach is used because the aim of the researcher is to explore the public view of sharia banking and sharia accounting in finding the difference between fact (reality) and essence (meaning) in fact (reality). The results of empirical research show that, firstly, the assessment of sharia banking practices in Indonesia is still far in the sense that not fully in accordance with Islamic Shari'ah is true. Secondly, the societal stereotype which considers that sharia accounting does not differ substantially with conventional accounting is true. Third, it turns out that the fundamental problem that causes the deviation of sharia practices from Islamic law is due to the factor of Human Resources (HR).